Peningkatan Keterampilan Berbicara dengan Strategi Mendeskripsikan di Kelas V - Sabti, Oni Audiandi; Mahyuddin, Ritawati; Zaiyasni, Zaiyasni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe the improvement of students' speaking skills with a strategy of describing in class V SDN 09 Air Tawar, Padang City. This research is a classroom action research (CAR) using a qualitative approach. This research was carried out at SDN 09 Air Tawar, Padang City with a total of 27 students consisting of 11 male students and 16 female students. The observations of the learning design in the first cycle obtained an average percentage of success of 90.67% increasing in the second cycle to 96.87%. Then the results of observations on the activities of teachers in the first cycle obtained an average percentage of success of 75% increased in the second cycle to 89.28%. Furthermore, the results of observations on the activities of students in the first cycle obtained an average percentage of success of 78.57% and increased in the second cycle to 92.85%. Keywords: speaking skills, strategies to describe